DUKUNGAN KELUARGA TERHADAP KELANGSUNGAN HIDUP ODHA (ORANG DENGAN HIV/AIDS) - Rahakbauw, Nancy (Jurnal Insani, 2016)
HIV/ AIDS problems have not been just as problem that happens at the local level, but these become the regional and global. This issue has caused a lot of casualties, both children and adults, and even has shocked family life. HIV has affected not only medically but also has an impact psychosocial-spiritual. If this condition is not dealt with quickly and appropriately, it will be very alarming. the Indonesia people will lose generations of productive young. Therefore, in order to suppress the spread of the virus it takes the involvement and support of various parties, especially families in the treatment and care so they who infected with HIV have a longer life.This study aimed to find out about their knowledge and understanding of people living with HIV/ AIDS (ODHA) and families on HIV disease and related issues as well as the forms of support provided by the families for ODHA in maintaining continuity their life. This study used a qualitative approach with descriptive analysis . The subject of research is HIV/ AIDS infected people and their families. The study found that knowledge and understanding of ODHA and their families is very limited, this is due to lack of information obtained about HIV / AIDS and related issues. This lack has impact on the process of treatment and care done by ODHA and families. It also affects ODHA to receive treatment from their families and the surrounding environment. Whereas the family support has a very significant meaning in the process of healing people living with HIV in living of worse times when he is sentenced infected with HIV. The support could also increase the life expectancy for people living with HIV.